PENGAWASAN PEMERINTAH DAERAH DALAM PENGENDALIAN PEREDARAN BAWANG MERAH IMPOR DI KABUPATEN BREBES TAHUN 2013 BERDASARKAN PERATURAN BUPATI BREBES NOMOR 20 TAHUN 2012 - Arief Yudha Prawira; Sulistyowati Sulistyowati; Lusia Astrika (Journal of Politic and Government Studies, 2015)
Onion is one of competitive commodities in Brebes Regency and the largest production center of onions in Indonesia. Of the total of onions national needs, 23% of it is supplied from Brebes Regency. The entry of onions imported from Thailand and Vietnam to Brebes Regency becomes a problem. Prices of local onion in Brebes Regency are increasingly rising, while the prices of imported onions are cheaper than the local ones. Farmers must face the reality that the quality of imported onions is currently similar to the local ones. The following is the comparison of local and imported onions in 2009. Brebes Regent Regulation Number 20 of 2012 is aimed at controlling the circulation of local onions in Brebes Regency. This study is aimed to describe any efforts made by local government to monitor the circulation of imported onions that can be detrimental to local farmers when selling local onions to the market. Due to the presence of imported onions, the prices of local onions will automatically be competed by the cheapness of imported ones. The result of the study shows that the central and local governments have been doing good supervision by monitoring stalls or central markets bimonthly to check whether there are any imported onions sold. It is recommended that all regencies should be able to commit to protect local products by establishing rules and regulations that control the entrance of imported commodities to traditional markets. Keywords: Imported Onions, Supervision of Circulation of Imported Onions, Brebes Regency.